ANALISIS PENDAPATAN PROYEK JALAN PADA PT. ARTHAMIX DI PALARAN - Chandra, Elvira Iravati (EKONOMIA, 2017)
The purpose of this study determine the suitability of recognition of revenue recognized by the company PT. ARTHAMIX Samarinda in accordance with Financial Accounting Standards Entities Without Accountability (SAK ETAP) About the construction contract. Based on the analysis and discussion of the PT. ARTHAMIX Samarinda in implementing the road project contract revenue in Percentage of Completion Method Palaran use with the system of fixed price contracts. The calculation of revenue recognition in 2013 by PT. ARTHAMIX Samarinda is Rp. 607.493.800,00 while according to the Financial Accounting Standards Entities Without Public Accountability (SAK ETAP) About the Project Contract street in Palaran Rp. 804.750.357,60 resulting in a difference of Rp. 197.105.257,60. Calculation of the recognition of receivables in 2013 by PT. ARTHAMIX Samarinda is Rp. 82.838.700,00 while according to the Financial Accounting Standards Entities Without Public Accountability (SAK ETAP) About Construction Contract Rp. 279.943.957,60 resulting in a difference of Rp. 197.105.257.60,00. The difference occurs because the percentage of completion method applied by PT. Samarinda ARTHAMIX not in accordance with the percentage of completion method in accordance with Financial Accounting Entities Without Public Accountability (SAK ETAP) On Road Projects In Palaran because the company did not make the costs of completion revenue recognition. Based on these conclusions above so the hypothesis that suggests Allegedly on revenue recognition Revenue Analysis by PT Samarinda ARTHAMIX not in accordance with Financial Accounting Entities Without Public Accountability (SAK ETAP) About Contract Road Project in Palaran that in calculating the revenue recognition received.